PENERAPAN KURVA TRIGONOMETRI UNTUK MOTIF KAIN BATIK - MEDIA PEMBELAJARAN PERSAMAAN TRIGONOMETRI - Endaryono Endaryono; Wirda Hidayah Azzahra (Department of Mathematics Education, Universitas Kuningan, 2022)
The subject of trigonometric equations is a learning material given to high school students majoring in Mathematics and Natural Sciences and also deepened in student lectures in the fields of science such as mathematics, engineering, informatics and others. The problem discussed in this study is that learning media is still needed to support learning trigonometric equations. The purpose of this research is to create a media for visual simulation of the results of trigonometric equation functions, namely the sine function with various equation models and by modifying the coefficient values in the equation. The results of this simulation are various curve images and are used as a choice of batik motifs. The research methodology uses mathematical modeling with trigonometric equations of sine functions. By changing some of the coefficients in the modification of the sine function, we get an interesting selection of images for batik patterns. The results of the study were in the form of a batik cloth motif design. This research can be used as an interesting learning medium on the subject of trigonometric equations and to addto the richness of various types of batik cloth motifs as an option for lovers of batik cloth art.